The TV industry: Advertising and programming - Tore Nilssen; Lars Sørgard (University of Oslo, Department of Economics, 2001)
The key to an understanding of the TV industry is the market for TV advertising. We present a model of this market that also encompasses the product markets and the viewer market. Because viewers dislike commercials, there is congestion in advertising, and TV channels offer complementary goods to advertisers. A move from a TV monopoly to a TV duopoly, we find, may reduce both the total number of viewers and the total amount of TV advertising. A softening of competition in each product market results in more investment in programming, higher price per advertising slot, and more advertising.
Keywords: L82; M37; L13; 330; Fernsehwerbung; Oligopol; Preiswettbewerb; Theorie